Patients’ Preference in Selecting a Dental Practitioner based on Gender: Gender Preferences in Choosing a Dentist - Aijaz Bhatti, Ayesha; Wasif, Fatima; Yousaf, Zarnab; Iqbal, Zunaira; Rafi Chaudhry, Asma; Zaffar, Sehrish (Journal of University College of Medicine and Dentistry, 2025)
Objective: To examine the prevalence of gender-based selection of dental practitioners among male and female patients in the Out Patient Department (OPD) of the Institute of Dentistry, CMH Lahore Medical College, and to identify factors influencing their choice. Methodology: A descriptive cross-sectional study was carried out in the OPD of the Institute of Dentistry, CMH Lahore Medical College, from April to July, 2024. A total of 303 participants, aged between 16 and 70 years, were selected through non-probability convenience sampling. The exclusion of dentists, dental students, medical doctors, and MBBS students was aimed at minimizing biases that could affect the results and limit the study’s generalizability. Data was collected using a validated questionnaire, assessed for reliability with Cronbach’s Alpha (α = 0.832), and analyzed using SPSS. Demographic information such as age, gender, marital status, and level of education was collected in the questionnaire to observe their effect on gender preference. The Chi-square test was used to assess the significance of differences between variables, with a P-value of less than 0.05 considered significant. Results: The mean age of participants was 32.4 years, with a gender distribution of 38.9% male and 61.1% female. Over half of the respondents (54.8%) had no specific gender preference while choosing a dentist. Key factors influencing dentist choice included experience, qualification, communication style, and accessibility. Among the female patients, 51 out of 185 wore Hijab as a part of a religious obligation. Out of these participants 59.7% indicated that it did not prevent them from seeking treatment from a male dentist. Conclusion: Overall, a majority (54.8%) of the patients did not have any gender preference. However, in general, female dentists were preferred for preventive and paediatric care, while male dentists were favoured for invasive procedures like extractions and prosthetics. Keywords: Gender Preferences, Gender Identity, Dentists, Patient-Dentist Relationship